Histological changes in the brain and liver of high-fat diet-fed male rats as a result of orlistat administration - S. Almuttairi, Rafah; M. Alzubaidy, Fakhir; Obeid Al-Taei, Alaa Hamady; Abdulhakeem, Zahraa Raad (Pharmakeftiki, 2025)
Obesity is a disorder characterized by excessive body weight gain. Orlistat is one of the medications used in the treatment of obesity, and acts by inhibiting gastric and pancreatic lipases. The objective of this study was to examine the short-term effects of orlistat on liver and brain tissues in rats fed a high-fat diet. In this study, 20 male albino rats (weighing approximately 193–212 g) were divided into two groups: group I (control group; consisting of five rats administered distilled water daily) and group II (orlistat group; comprising 15 rats given a daily oral dose of orlistat at a dose of 32 mg/kg body weight per day, via gastric tube, for 10 weeks). At the end of the experimental period, the animals were sacrificed, and the liver and brain tissues were prepared for histological analysis. Rats treated with orlistat exhibited degenerative changes in both liver and brain tissues compared to the control group. In the liver, these changes included dilation, blood vessel congestion, and lymphocyte infiltration. In the brain, the observed changes were characterized by the infiltration of neutrophils or mononuclear leukocytes. In conclusion, orlistat exerts harmful effects on liver and brain tissues; therefore, its clinical use should be closely monitored.